Do you hear the people sing? Comparison of synchronized URL and narrative themes in 2020 and 2023 French protests - Ng, Lynnette Hui Xian; Carley, Kathleen M. (Frontiers in Big Data, 2023)
France has seen two key protests within the term of President Emmanuel Macron: one in 2020 against Islamophobia, and another in 2023 against the pension reform. During these protests, there is much chatter on online social media platforms like Twitter. In this study, we aim to analyze the differences between the online chatter of the two years through a network-centric view, and in particular the synchrony of users. This study begins by identifying groups of accounts that work together through two methods: temporal synchronicity and narrative similarity. We also apply a bot detection algorithm to identify bots within these networks and analyze the extent of inorganic synchronization within the discourse of these events. Overall, our findings suggest that the synchrony of users in 2020 on Twitter is much higher than that of 2023, and there are more bot activity in 2020 compared to 2023.